Developing A Reform-Oriented Medical Takaful (Islamic Insurance) Model for Nigeria’s Sustainable Development - Rauf Adeola Lateef; Asamu Rasheed Adebimpe; Salami Idris Olawale (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to examine the potential of a reform-oriented Medical Takaful model as an alternative healthcare financing system in Nigeria by assessing public awareness, acceptability, and the development of a sustainable and Shariah-compliant healthcare model. Theoretical framework: The study is based on Islamic finance principles, particularly ta’awun (cooperation), risk-sharing, and maqasid al-shariah, alongside sustainable development theory focusing on equitable healthcare access and social welfare. Literature review: Previous studies show that Nigeria faces challenges such as low insurance coverage, high out-of-pocket healthcare costs, and weak healthcare financing systems. Research also indicates that Takaful has been effective in countries like Malaysia and Indonesia, although its implementation in Nigeria remains limited due to poor awareness and regulatory challenges. Methods: The study adopted a mixed-methods approach using questionnaires distributed to 300 respondents and interviews with Islamic scholars, healthcare professionals, and insurance experts. Data were analyzed using descriptive statistics and thematic analysis. Results: The findings revealed low medical insurance coverage but high interest in Islamic-compliant healthcare financing. Major challenges identified include poor awareness, lack of trust, and inadequate policy support. Most respondents expressed willingness to participate in a properly regulated Medical Takaful scheme. Implications: The study suggests that Medical Takaful can improve healthcare access, reduce out-of-pocket expenses, and support sustainable development goals through inclusive and ethical healthcare financing. Novelty: The study proposes a reform-oriented Medical Takaful model specifically designed for Nigeria’s socio-economic and religious context by combining Islamic principles with modern healthcare financing strategies.